IPTEKS PENERAPAN AKUNTANSI KAS KECIL PADA PT. PLN (PERSERO) RAYON MANADO SELATAN - Usman, Yuliasari; Rondonuwu, Sintje (Universitas Sam Ratulangi, 2018)
The application of petty cash accounting for companies is very important because with the existence of petty cash each company activities will run more efficiently. The use of small cash accounts is considered by some companies to be very helpful in the company's operations that are important and fast needed so that the use of small cash accounts is more efficient than cash accounts. PT. PLN South Manado Rayon also uses or applies small cash accounting because the Rayon Unit itself requires important and fast management needed so that it cannot use a cash account whose expenditure requires checks or demand deposits. This study explains how the application of petty cash at PT. PLN South Manado Rayon and use what recording method for petty cash itself.Keywords: Petty Cash, Recording and Reporting Methods